Effects of monetary policy communication in emerging market economies: Evidence from Malaysia - Sui-Jade Hoand; Özer Karagedikli (Philipps-University Marburg, School of Business and Economics, 2021)
By conducting a high-frequency event study similar to Gürkaynak et al.(2005), we find that two factors are needed to adequately capture the effects of monetary policy announcements for a non-inflation targeting emerging market economy, Malaysia. These factors are the surprise changes inthe policy rate (Overnight Policy Rate, OPR) and the information aboutthe future path of monetary policy. We find that the path factor has astrong influence on long-term government bond yields, corporate bondyields and spreads. Our findings are indicative of the view that monetarypolicy communication is mostly about revealing information pertaining tothe central bank's assessment of the economic outlook, as opposed to anunconditional binding commitment to follow a specific policy path.
Keywords: J31; J64; 330; Geldpolitik; Politische Kommunikation; Wirkungsanalyse; Malaysia